The Theory of Ratification and Proscription from the perspective of Sunnis - Hussein Rajabi / Mehdi Norouzi / Mahdi Sedaqat ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The issue of Ratification and Proscription is one of issues in which the dispute occurred between scholars of the fundamentals of the various Islamic schools of thought in the past and the present. The point of contention in this issue is regarding the subsidiary legal rulings and legal matters, not real and rational matters. This research is of particular importance, and it has multiple jurisprudential and jurisprudential results, especially in the issue of partiality. What is known among a group of scholars of the fundamentals is that all Sunni scholars are followers of the theory of Ratification in opposition to the Imam scholars as they are Proscription, but by referring to the fundamental books of the Sunnis, it can be noted that the attribution of the statement of correction to all of their scholars is not correct. Rather, it can be said that many of them are Proscription, due to the importance and the role of choosing the most accurate sayings in the deductions of Islamic jurists, we have briefly addressed in this article a statement and review of the evidence of public scholars on the issue of Ratification and Proscription. Our research has taken the descriptive and analytical method, with a thorough investigation, in order to reach the desired results. DOI /10.54633/2333-021-042-009